“Talking the Same Language”: The Influence of Sharing a Visual Impairment Identity Between Researchers and Participants on Enhancing Participant Recruitment and Fostering Rapport During Interviews With Blind Individuals - Ibrahim Emara (International Journal of Qualitative Methods)
Interviews are increasingly being recognized as a valuable data collection method among researchers conducting studies involving individuals with visual impairments. Conducting interviews with individuals who are visually impaired raises diverse ethical, methodological, and theoretical concerns. However, several compelling questions remain unresolved, such as: Should qualitative researchers belong to the population they are studying, such as being visually impaired when researching the experiences of visually impaired individuals? Is a blind individual’s willingness to participate in interviews influenced by whether the interviewer has a visual impairment or not? Does a researcher’s membership within the group being studied ensure the establishment of strong rapport? What are the recommended guidelines for establishing rapport with blind individuals during interviews? Using autoethnography, I will share my personal experiences and those of other researchers investigating visually impaired people in establishing rapport with blind interview subjects. The article will provide insights into the principles of rapport building, informed by the perspectives of ten disability scholars who have conducted interviews with blind individuals. I contend that when researchers share the same identity as the community they are studying, the number of study participants tends to increase. Additionally, the sense of rapport between researchers and participants is significantly enhanced. Consequently, the article makes several significant contributions that benefit both blind and sighted researchers. It equips them with techniques and strategies for interacting effectively with visually impaired individuals during interviews.